Chromosomal reference genome sequences for the malaria mosquito, Anopheles coustani, Laveran, 1900 [version 1; peer review: 2 approved] - Shane A. McCarthy; Damon-Lee B. Pointon; Jonathan M.D. Wood; Ying Sims; James W. Torrance; Mara K N Lawniczak; Marcela Uliano-Silva; Martin G. Wagah; Diego Ayala; Harriet F. Johnson; Ksenia Krasheninnikova; Haynes Heaton; et al. (Wellcome Open Research, 2024)
We present genome assembly from individual female An. coustani (African malaria mosquito; Arthropoda; Insecta; Diptera; Culicidae) from Lopé, Gabon. The genome sequence is 270 megabases in span. Most of the assembly is scaffolded into three chromosomal pseudomolecules with the X sex chromosome assembled for both species. The complete mitochondrial genome was also assembled and is 15.4 kilobases in length.